2012
DOI: 10.1016/j.ympev.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus species tree analyses resolve the radiation of the widespread Bufo bufo species group (Anura, Bufonidae)

Abstract: species tree analyses resolve the radiation of the widespread Bufo bufo species group (Anura, Bufonidae), Molecular Phylogenetics and Evolution (2011),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
107
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 56 publications
(43 reference statements)
8
107
0
1
Order By: Relevance
“…dalmatina samples from Serbia were well separated from others collected in Spain, Moldova, France and Germany. In the B. bufo clade, samples from Serbia were placed together with those from Greece, Italy, Austria and Croatia, but somewhat apart from the sample from Portugal, being in line with the results of Recuero et al (2012) who revealed that common toads from the Iberian Peninsula belong to B. spinosus, while Appenine, Central European and Balkan ones represent B. bufo.…”
Section: Discussionsupporting
confidence: 87%
“…dalmatina samples from Serbia were well separated from others collected in Spain, Moldova, France and Germany. In the B. bufo clade, samples from Serbia were placed together with those from Greece, Italy, Austria and Croatia, but somewhat apart from the sample from Portugal, being in line with the results of Recuero et al (2012) who revealed that common toads from the Iberian Peninsula belong to B. spinosus, while Appenine, Central European and Balkan ones represent B. bufo.…”
Section: Discussionsupporting
confidence: 87%
“…Across the core outbreak region of the Western Pyrenees, the midwife toad ( Alytes obstetricans ) experiences annual mass mortality due to chytridiomycosis. Two other anuran species also commonly breed in this area, the common toad ( Bufo spinosus, previously known as Bufo bufo [21]) and the common frog ( Rana temporaria ). Across Europe, the prevalence of Bd within affected common toads is usually low [14], with the majority of individuals tolerating infection [22].…”
Section: Introductionmentioning
confidence: 99%
“…[20, 21]). Here we focus on the East-Asian tree frogs ( Hyla japonica group; recently changed to Dryophytes japonicus [22]), which offer an excellent opportunity to advance our historic biogeographic knowledge on this region.…”
Section: Introductionmentioning
confidence: 99%